APPLYING INTERVENTIONS TO ENHANCE KNOWLEDGE OF MALAYSIAN CULTURAL ART FORMS - Yip, Jinchi; Daniel, Esther Gnanamalar Sarojini; De Witt, Dorothy (PEOPLE: International Journal of Social Sciences, 2020)
In graphic design education, students are trained for the industry through practising and applying graphic design principles in various classroom and real life projects. While possessing the knowledge of these principles is important, the researcher, through her experience as a graphic design educator in Malaysia, finds that Malaysian students also need to have some knowledge and understanding of their own local, cultural art forms. This is because it could open more doorways for a designer to produce creative ideas that would be more relevant to the local audience. Therefore, in order to enhance her students’ knowledge and understanding of some Malaysian cultural art forms, the researcher used a case study action research method and applied interventions in her classroom of 20 graphic design students, underpinned by Cultural Responsive Teaching pedagogy. Various activities were carried out to scaffold students’ learning of the selected Malaysian cultural art forms. The activities were, a visit to a contemporary Malaysian art exhibition; participation in a batik workshop; a visit and hands-on experience making some craft work at a Mah Meri cultural village, and attending a talk about wayangkulit, as well as viewing some wayangkulit exhibits. Upon the completion of all activities, the students produced a work of design based on a local social/environmental/health issue of their choice. The researcher sought to find out if the students applied their knowledge of Malaysian cultural art forms into their work of design. Findings from studying the students’ design work show that not all of them applied the knowledge that they had gained from the activities. However, through focus group interviews, most students express that their knowledge has been enriched by participating in those activities.